1994
DOI: 10.1079/bjn19940195
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and micronutrient status of adolescents: effect of vitamin and trace element supplementation on indices of status and performance in tests of verbal and non-verbal intelligence

Abstract: Relationships between micronutrient intake and status, and micronutrient status and performance in tests of intelligence were investigated in a group of adolescents (13-14 years old). Dietary intakes were assessed using a 7 d weighed dietary record method, coupled with the collection of duplicate diets.Vitamin and trace mineral intakes calculated using food composition tables were compared with those obtained by direct analysis of duplicate diets. Micronutrient status was judged via a range of biochemical indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 33 publications
4
36
1
3
Order By: Relevance
“…This is still largely true of the latest edition of the food tables (Holland et al, 1991) since only a portion of the data has been produced by more modern HPLC methods. Using directly analysed vitamin B 6 intakes no correlation was found between intake and plasma PLP values in female adolescents, but there was a signi®cant correlation for boys (r 0.56, P`0.05; Southon et al, 1994, Bailey et al, 1997. Schuster et al (1984) found a positive correlation between PLP and vitamin B 6 intake from the previous day.…”
Section: Plasma Plp Concentrations In Human Population Groupsmentioning
confidence: 90%
“…This is still largely true of the latest edition of the food tables (Holland et al, 1991) since only a portion of the data has been produced by more modern HPLC methods. Using directly analysed vitamin B 6 intakes no correlation was found between intake and plasma PLP values in female adolescents, but there was a signi®cant correlation for boys (r 0.56, P`0.05; Southon et al, 1994, Bailey et al, 1997. Schuster et al (1984) found a positive correlation between PLP and vitamin B 6 intake from the previous day.…”
Section: Plasma Plp Concentrations In Human Population Groupsmentioning
confidence: 90%
“…Published intervention studies have mainly investigated the effect of nutrient supplements and the presence/absence and content of the breakfast meal on a range of subjective and objective learning outcomes (Dickie and Bender, 1982;Meyers et al, 1989;Southon et al, 1994;Wolraich et al, 1994;Rampersaud et al, 2005;Dalton et al, 2009;Micha et al, 2010). Few studies have addressed the relationship between school lunch consumption and educational outcomes (Gietzen and Vermeersch, 1980;Kim et al, 2003;Florence et al, 2008;Selvik Ask et al, 2010) and no study has focussed on classroom behaviour in the post-lunchtime period.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The B group vitamins are very important water-soluble vitamins that play vital roles in metabolism, and their absences are associated with serious diseases. 5,6 The human diet sometimes does not meet the daily requirements of vitamins necessary to maintain body functions and normal development.…”
Section: Introductionmentioning
confidence: 99%